Determinant Factors of Low Back Pain in Paving Block Workers - Khayan, Khayan; Hyasinta, Hyasinta; Anwar, Taufik; Puspita, Widyana L; Wardoyo, Slamet; Hanif, Muhammad Ifham (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Paving block workers are included in the informal sector and have a risk of lower back pain. Documenting the workers’ health status in the informal sector has not been done well so that workers do not get protection from the government. Heavy physical work puts pressure on the spine associated with repeated body twisting. This study aims to determine work attitude, length of employment, and exercise habits related to low back pain in Pontianak paving block workers in 2018. This type of research is observational with a cross-sectional approach. Sampling uses total sampling. The research sample of 56 paving block workers in the city of Pontianak, West Kalimantan. Data is processed with a computer program. Data analysis was performed univariate and bivariate and tested using the Chi-square test, with α = 5%. The results showed that there was a significant relationship between the length of the work (p = 0.013), work attitude (p-value = 0.038), and exercise habits (p = 0.003) with low back pain.